Solution-processable perylene diimide-based electron transport materials as non-fullerene alternatives for inverted perovskite solar cells. Issue 20 (27th April 2022) - Perez, German Soto; Dasgupta, Shyantan; Żuraw, Wiktor; Pineda, Rosinda Fuentes; Wojciechowski, Konrad; Jagadamma, Lethy Krishnan; Samuel, Ifor; Robertson, Neil
Abstract : Bay-functionalised perylene diimides were synthesised and as electron-transport layer in inverted perovskite solar cells gave efficiency up to 16.8%. Abstract : Perylene diimide derivatives with different functional groups (OR) in the bay position were synthesised (PDI-1, OR = OC6 H4 OMe; PDI-2, OR = OC6 H4 CH2 CH2 NHBoc; PDI-3, OR = OC6 H4 CO2 Me) and their optoelectronical properties were characterised. The derivatives were applied as alternative electron transport materials (ETMs) to replace the commonly used PCBM in inverted perovskite solar cells (PSCs). Devices with the structure ITO/PTAA/Cs0.04 (MA0.17 FA0.83 )0.96 Pb(I0.83 Br0.17 )3 /ETM/Ag (ETM = PCBM or PDI-1, -2 or -3) were fabricated through solution processing techniques. A competitive power conversion efficiency (PCE) of 16.8% was obtained for the PDI-3-based device, which was comparable to the PCBM-based device with PCE of 17.3%. It was found that the electronic nature of the functional groups plays an important role in the charge extraction and band alignment of these small molecular semiconductors.